Прогноз та вивчення адаптивних стратегій тропічних і субтропічних рослин при інтродукції - Gornitska, І.Р. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
A new approach to determination of the adaptive strategies are proposed for the presentatives of tropical and subtropical zones of vegetation grown in greenhouses by the geological-botanical-geographical method. Mobilization centers are determined and prognosis of plant introduction are made on the basis of the formation of geoclinical belts of Earth.